Sign theory at work: The mental imagery debate revisited - Issajeva, Jelena (Sign Systems Studies, 2015)
This article attempts to give a plausible explanation to the long-debated question about the nature of mental imagery (MI). The traditional approach to this question is based on the representational paradigm, which, I claim, is misguided. Instead of representational aspects of mental imagery, I emphasize the functions of mental imagery, the variety of properties that images exhibit in experimental studies, and the relations between different characteristics of images, their functions and the subject of imagery. That is, I propose to account for mental imagery as a sign system, consisting of different types of signs. A mental image can contain important properties as parts of the complex sign. This approach to the explanation of the nature of MI is beneficial, since it suggests the phenomenon of mental imagery, which overcomes some long-standing controversies on the issue.